The Impact of Blended Learning On University Education: Advancements in Technology and Learners’ Performance - Asma Ishtiaq; Dr. Shamaiela Farooqi; Dr. Shafqat Rasool, (Dialogue Social Science Review (DSSR), 2025)
Modern technological breakthroughs have a huge influence on teaching and learning. The present study aims to address the research question, "Would using technology enhance and encourage autonomous learning while also enhancing student engagement?" A blended learning strategy was utilised in a business course to evaluate this. The mix of face-to-face and online learning sessions is referred to as "blended learning." The article reflects on the comprehensive findings of a research undertaken at the university level to analyse the influence of a blended learning effort on student involvement and overall. It also obtains students' opinions on the blended learning strategy. The survey approach was used to perform the quantitative investigation. SPSS software was used to analyse the findings. The data clearly reveal that students in the test group (where blended learning was implemented) learnt more in terms of accomplishment of learning outcomes and general engagement with online and in-class activities. The evidence supporting blended learning's good effects has been identified; it leads to improved student success and promotes student engagement. Students had a larger proportion of cognitive involvement than emotional engagement, with mean and standard deviation values of 4.13 and 1.40, respectively. Based on the findings, the study adds to the literature on blended learning by demonstrating its good outcomes. There are serious ramifications for both the teacher and the institutions who want to employ a blended learning method. As a result, serious higher education changes may be the government's future course.